2021
DOI: 10.5534/wjmh.190145
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Improves Sperm Parameters, Oxidative Stress Markers and Sperm DNA Fragmentation in Infertile Patients with Idiopathic Oligoasthenozoospermia

Abstract: Purpose: Oxidative stress and sperm DNA fragmentation (SDF) are potential contributing factors for idiopathic male infertility. Coenzyme Q10 (CoQ10) have been reported to be effective in the treatment of idiopathic male infertility, in general, owing to its antioxidant properties. Thus, the present study intends to investigate the effects of CoQ10 therapy on semen parameters, oxidative stress markers and SDF in infertile men, specifically with idiopathic oligoasthenozoospermia (OA). Materials and Methods: In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 27 publications
6
55
0
2
Order By: Relevance
“…L‐Carnitine and coenzyme Q10 are powerful antioxidants that prevent LPO and SDF. Meta‐analysis and other studies showed that both compounds improved conventional sperm parameters 118‐122 . Several studies on supplementation with a combination of antioxidants have also been reported 123‐125 .…”
Section: Management and Prevention For Mosimentioning
confidence: 89%
See 1 more Smart Citation
“…L‐Carnitine and coenzyme Q10 are powerful antioxidants that prevent LPO and SDF. Meta‐analysis and other studies showed that both compounds improved conventional sperm parameters 118‐122 . Several studies on supplementation with a combination of antioxidants have also been reported 123‐125 .…”
Section: Management and Prevention For Mosimentioning
confidence: 89%
“…Meta-analysis and other studies showed that both compounds improved conventional sperm parameters. [118][119][120][121][122] Several studies on supplementation with a combination of antioxidants have also been reported. [123][124][125] These antioxidant therapies and outcomes were shown in possible toxic effect when overused.…”
Section: Shorter Interval Of Ejaculatory Abstinencementioning
confidence: 99%
“…Mercury (217.216 ppm; 800 μΜ) has been reported to significantly (p < 0.001) increase (12.0% compared to 2% in control) percentage of DNA breaks in human sperms 42 . Positive correlation between sperm DNA fragmentation and levels of ROS has been reported in testicular tissue of mice 43 and semen of humans 44,45 . TUNEL assay in the present study revealed that mercuric chloride at lower concentration (0.031 µg/ml) did not induce any DNA damage in sperm cells even after 3 h of exposure.…”
Section: Correlation Between Dna Damage Apoptosis and Necrosis Datamentioning
confidence: 87%
“…The authors reported a significant improvement of sperm analysis parameters (sperm concentration, progressive motility and total motility) compared to the baseline levels recorded before the beginning of treatment. Furthermore, CoQ 10 supplementation increased the total antioxidant capacity and the glutathione peroxidase levels, with a consequent reduction in ROS levels and in the sperm DNA fragmentation index [ 188 ]. Similar results concerning the amelioration in sperm concentration, motility, and antioxidant status, were also obtained in the third study, in which 35 infertile males with idiopathic oligoasthenozoospermia were administered 200 mg/day of CoQ 10 H 2 [ 189 ].…”
Section: Antioxidant-based Therapies In the Treatment Of Male Infementioning
confidence: 99%